Substitution of Fish Meal with Chicken Feather Silage Meal on Feed Can Improve Growth Performance of Striped Catfish (Pangasius hypopthalmus) - Diana rachmawati; Istiyanto Samidjan; Dicky Harwanto; Hadi Pranggono (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
The purpose of this research is to study the effect of substitution of fish meal with silage meal of chicken feathers on feed to protein digestibility, growth and survival rate of striped catfish (Pangasius hypopthalmus). The test fish used is catfish with an average weight of 2.31 ± 0.04 grams /fish. This research used experimental method with Completely Randomized Design, 5 treatments in triplicate. The treatments in this study were substitution of fish meal meal with different dose of chicken feather meal, namely A, B, C, D and E (0%; 25%; 50%; 75% and 100% silage meal of chicken feathers, respectively). Parameters observed included relative growth rate (RGR), feed conversion ratio (FCR), protein efficiency ratio (PER), Apparent Digestibility Coefficient of Protein (ADCP), and survival rate (SR) of catfish. The results showed that the substitution of fish meal with chicken feather silage meal was very significant (P <0.01) to RGR, FCR, PER, and ADCP, but no significant effect (P> 0.05) on SR of catfish. Dose 25% silage chicken feather meal in the feed is the best dose to improve the RGR and ADCP of catfish. Water quality during the study is still within a reasonable range for catfish culture.